In vitro and in vivo assessment of wound healing properties of peri-vitelline fluid extracted from fertilized eggs of Asian horseshoe crab, Tachypleus gigas (Muller 1785) - Mat Isa, Mohamad Faizul (2017)
Horseshoe crab is an ancient species existed 475 million years ago. The discovery on the precious compound of its blood, the amebocyte lysate, has benefited human kind contributing to the development of an endotoxin detection kit. Ever since then various studies have been carried out on this species, particularly in its life cycle how it impacted other life forms. This study focuses on the less studied aspect, the peri-vitelline fluid (PVF) of its eggs. Void of parental care, the horseshoe crab embryo developed with nourishment solely from PVF. This observation suggests that this PVF may contain beneficial property towards tissue regeneration. Hence, PVF of a local horseshoe crab, Tachypleus gigas was investigated for its wound healing ability. The first part of this study was conducted to screen the biochemical composition through proximate analysis (protein, fat, carbohydrate, ash, moisture and energy), minerals contains (arsenic, antimony, cadmium, lead, mercury, stanum, copper, zinc, calcium, iron, potassium, magnesium, manganese, sodium, phosphorus, selenium, chromium and nickel) in PVF and embryo at 4th embryonic stage. While protein screening was carried on PVF extracted from 3rd and 4th embryonic stages. The next part was on the in vitro study to determine the viability of 3T3 (mouse skin fibroblast cell) cells using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium and migration assay. Experiments were conducted using eight concentrations (1.56 to 200 μg/mL) of PVF for 72 hours. Then, in vivo study was carried out on brine shrimp and Sprague dawley rats. Toxicity tests on brine shrimps were using PVF with concentration of 1.85 to 1000 μg/mL. Experiment on rats was conducted with treatment consisted of 0.9% saline, petroleum jelly, Solcoseryl jelly 10%, PVF of 3rd embryonic stage 100 and 200 mg/g, PVF of 4th embryonic stage 100 and 200mg/g. Rats inflicted with wound then treated with the above treatments for 15 days. Rats were then euthanized and sacrificed, skin, liver and kidneys collected for histological study. Proximate analysis on the PVF of 4th embryonic stage for protein, fat, carbohydrate, ash, moisture and energy were 0.5 mL/100 mL, 0 mL/100 mL, 0.3 mL/100 mL, 3.0 mL/100 mL, 96.2 mL/100 mL and 1.4 Kcal/100g, respectively, while for the embryo of 4th embryonic stage 59.2 mL/100 mL, 12.1 mL/100 mL, 12.9 mL/100 mL, 9.4 mL/100 mL, 6.4 mL/100 mL 397 Kcal/100g, respectively. Protein screening on the PVF samples showed that the 3rd embryonic stage has more protein spots compared to the 4th stage. The pattern of the protein spots also differs between these two embryonic stages. Based on the in vitro study, PVF was found to be non-toxic to 3T3 cells with 80% viability for all the tested concentrations. In the migration assay, PVF dosages of 100 and 200 μg/ mL for the two embryonic stages (3rd and 4th) showed 100% migration of 3T3 cells after 24 hours as compared to positive control (0.5% silver sulfadiazine). Toxicity test showed non-toxic effects on the brine shrimps for all the PVF dosages (1.95 to 1000 μg/mL). The rats treated with PVF from the 3rd embryonic stage at 100 mg/g and 4th embryonic stage at 200 mg/g showed accelerated healing, earlier by 3 days as compared to positive control (Solcoseryl gel 10%). While, the wounds treated with PVF at 200 mg/g from the 3rd and 4th embryonic stages healed well internally without adverse effect on the livers and kidneys. The finding of this study showed that the PVF extracted from the T. gigas eggs has beneficial property to support the rapid healing of wound without detrimental effect on the rat. It can be concluded that PVF of T. gigas has potential to be used as treatment to accelerate healing of wound particularly in patients with slow recovery.